Ambient Games, Revealing a Route to a World Where Work is Play?. (12th February 2008) - Eyles, Mark; Eglin, Roger
Abstract : A novel way of playing games called ambient gaming is defined and described. Growing out of ideas in ambient music, ambient gaming is defined as "ignorable as it is interesting" after Brian Eno's description of ambient music. Ambient gaming is set in the context of existing games. Further, ambient games are set in a technological context, showing that the technology enabling their development is now becoming available. The specification and implementation of an ambient game prototype, Ambient Quest, are described. Finally, future directions leading to work enhancing games are suggested.